Lost without a trace: the employee’s employment status - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2014)
The issue considered in this article is whether the employment relationship of an employee may be terminated on grounds of frustration of contract in a situation where the employee mysteriously disappears without a trace or his whereabouts is unknown. If the answer to the above is in the affirmative, what is the reasonable period before the employer can resort to terminating the employment relationship? For example, Malaysia Airlines flight MH370 mysteriously disappeared with many employees on board. As there was no proof of the sighting of wreckage of the airplane, it is difficult to assume that the airplane had crashed and those on board had died. In the aforesaid circumstances, the employment status of those employees on board arises and what a prudent employer should do in the given scenario. Again, the recent case where an employee never returned after an outstation trip, the employer would be in a dilemma of whether to continue his employment status or to terminate the employment relationship. This is due to the fact that the cause of his disappearance is unknown.